FTO levels affect RNA modification and the transcriptome - Berulava, Tea (Nature Publishing Group, 2013)
A block of single-nucleotide polymorphisms within intron 1 of the FTO (fat mass and obesity associated) gene is associated with variation in body weight. Previous works suggest that increased expression of FTO, which encodes a 2-oxoglutarate-dependent nucleic acid demethylase, leads to increased body weight, although the underlying mechanism has remained unclear. To elucidate the function of FTO, we examined the consequences of altered FTO levels in cultured cells and murine brain. Here we show that a knockdown of FTO in HEK293 cells affects the transcripts levels of genes involved in the response to starvation, whereas overexpression of FTO affects the transcript levels of genes related to RNA processing and metabolism. Subcellular localization of FTO further strengthens the latter notion. Using immunocytochemistry and confocal laser scanning microscopy, we detected FTO in nuclear speckles and – to a lesser and varying extent – in the nucleoplasm and nucleoli of HEK293, HeLa and MCF-7 cells. Moreover, RNA modification analyses revealed that loss of Fto affects the 3-methyluridine/uridine and pseudouridine/uridine ratios in total brain RNA. We conclude that altered levels of FTO have multiple and diverse consequences on RNA modifications and the transcriptome.